2012
DOI: 10.1080/10503307.2012.688884
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to change as a moderator of outcome in transdiagnostic treatment

Abstract: Initial symptom severity is a client characteristic associated with psychotherapy outcome, although this relationship is not well-understood. Readiness to change is a factor that may influence this relationship. This study tested readiness as a moderator of the relationship between initial severity and symptom change. Data were derived from an RCT examining the efficacy of a transdiagnostic CBT treatment. Readiness was assessed with the URICA, and symptom and functioning outcomes were assessed. Multiple regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 45 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…An interesting variable to investigate in the context of early treatment response might be readiness to change. Boswell et al (2012), for example, found that readiness to change moderated the relationship between pre- and post-treatment levels of depression and anxiety. The highly negative association between levels of pre-treatment impairment and pre-to-post change was reversed for patients with higher levels of readiness to change.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting variable to investigate in the context of early treatment response might be readiness to change. Boswell et al (2012), for example, found that readiness to change moderated the relationship between pre- and post-treatment levels of depression and anxiety. The highly negative association between levels of pre-treatment impairment and pre-to-post change was reversed for patients with higher levels of readiness to change.…”
Section: Discussionmentioning
confidence: 99%
“…University of Rhode Island Change Assessment —This 28‐item self‐report instrument measured an individuals’ motivational readiness to change their drug use behavior. Individuals respond to a series of statements with respect to how much they agree or disagree (along a 5‐point scale), with the overall “readiness” score most commonly reported …”
Section: Methodsmentioning
confidence: 99%
“…Individuals respond to a series of statements with respect to how much they agree or disagree (along a 5-point scale), with the overall "readiness" score most commonly reported. 24…”
Section: Assessmentsmentioning
confidence: 99%
“…Willingness to change problematic behaviour was found to be a moderator in a study of transdiagnostic face-to-face treatment (Boswell et al, 2012) as well as in an uncontrolled study of face-to-face treatment for participants with somatoform disorders (Heider et al, 2017). Additionally, the "action"-subscale of willingness to change was found to moderate the effect of an online intervention addressing marijuana use among students (Palfai et al, 2016).…”
Section: Introductionmentioning
confidence: 92%